2019
DOI: 10.1021/acschemneuro.9b00094
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerization Effect of Histidines on Oligomer Aggregation of β-Amyloid(1–40/42) during the Early Stage: Tautomerism Hypothesis for Misfolding Protein Aggregation

Abstract: As the intrinsic origin of the hypothesis for β-amyloid (Aβ) from Alzheimer’s disease, histidine behaviors were found to play a crucial role in Aβ aggregation. To investigate the histidine behaviors during the early stage of aggregation, Aβ40/42 pentamers with different histidine isomer states were simulated at the atomic level. Results show that five Aβ40 (δδδ) and Aβ42 (εδδ) monomers can rapidly decrease the aggregation threshold, promote stable pentamer formation, and increase pentamer contents by 51.8% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 44 publications
8
33
0
Order By: Relevance
“…Shi et al (9) have used molecular dynamics (MD) simulations to demonstrate the tautomer effects of the Ab (1-40) peptide, which, when containing the His6(d)-His13(d)-His14(d) isomer (the so-called ddd isomer), leads to the formation of greater amounts of antiparallel b-sheets between the central hydrophobic center (CHC) and C-terminus compared with the other seven isomers (ddε, dεd, dεε, εεε, εεd, εdε, εdd). Our previous simulation studies regarding homodimers (12) and pentamers (13) confirmed such trends. However, the effect of tautomeric state of histidine within Ab requires clarification.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Shi et al (9) have used molecular dynamics (MD) simulations to demonstrate the tautomer effects of the Ab (1-40) peptide, which, when containing the His6(d)-His13(d)-His14(d) isomer (the so-called ddd isomer), leads to the formation of greater amounts of antiparallel b-sheets between the central hydrophobic center (CHC) and C-terminus compared with the other seven isomers (ddε, dεd, dεε, εεε, εεd, εdε, εdd). Our previous simulation studies regarding homodimers (12) and pentamers (13) confirmed such trends. However, the effect of tautomeric state of histidine within Ab requires clarification.…”
Section: Introductionsupporting
confidence: 71%
“…A total of three types of models-histidine residue, histidine residue with implicit water, and the histidine dipeptide (same as classical MD model)-were considered. To distinguish two amide-I bonds of histidine dipeptide models, the amide-I bond located at the C-terminus was isotope labeled with C 13 and O 18 . The geometric structures were fully optimized, and anharmonic frequency calculations were carried out using the keyword freq¼anharmonic, which uses numerical differentiation along modes, to determine the vibrational transitions of the amide-I bond.…”
Section: Quantum Calculationmentioning
confidence: 99%
“…Several kinds of research to determine the neutral histidine tautomerism effect on the misfolding of β‐amyloid peptide and tau protein for the pathogenesis of proteinopathies have been performed by our group [20,21] . In line with the introduced histidine tautomerism hypothesis on β‐amyloid aggregation, [22] those results implied the significant role of tautomerism in early oligomerization and structural changes. However, the intrinsic origin of hIAPP accumulation due to distinct histidine behaviors remains largely unclear.…”
Section: Introductionsupporting
confidence: 73%
“…The tautomeric state of the histidine residues in the Aβ42 peptide is (εεε). The role of the tautomeric state of the histidine residues in the aggregation properties of the Aβ40 and of the Aβ42 monomers was studied by Brännström et al [49] and by Lee and coworkers [50,51], respectively. Their results show a preference of the (εεε) isomer of the H6-H13-H14 residues to trigger β-sheet-folding.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%